Using Health Information Technology to Engage African American Women on Nutrition and Supplement Use During the Preconception Period - Gardiner, Paula; Bickmore, Timothy; Yinusa-Nyahkoon, Leanne; Reichert, Matthew; Julce, Clevanne; Sidduri, Nireesha; Martin-Howard, Jessica; Woodhams, Elisabeth; Aryan, Jumana; Zhang, Zhe; Fernandez, Juan; Loafman, Mark; et al. (Frontiers in Endocrinology, 2021)
ABSTRACT IMPORTANCE: Healthy nutrition and appropriate supplementation during preconception have important implications for the health of the mother and newborn. The best way to deliver preconception care to address health risks related to nutrition is unknown. METHODS: We conducted a secondary analysis of data from a randomized controlled trial designed to study the impact of conversational agent technology in 13 domains of preconception care among 528 non-pregnant African American and Black women. This analysis is restricted to those 240 women who reported at least one of the ten risks related to nutrition and dietary supplement use. INTERVENTIONS: An online conversational agent, called “Gabby”, assesses health risks and delivers 12 months of tailored dialogue for over 100 preconception health risks, including ten nutrition and supplement risks, using behavioral change techniques like shared decision making and motivational interviewing. The control group received a letter listing their preconception risks and encouraging them to talk to a health care provider. RESULTS: After 6 months, women using Gabby (a) reported progressing forward on the stage of change scale for, on average, 52.9% (SD, 35.1%) of nutrition and supplement risks compared to 42.9% (SD, 35.4) in the control group (IRR 1.22, 95% CI 1.03-1.45, P = 0.019); and (b) reported achieving the action and maintenance stage of change for, on average, 52.8% (SD 37.1) of the nutrition and supplement risks compared to 42.8% (SD, 37.9) in the control group (IRR 1.26, 96% CI 1.08-1.48, P = 0.004). For subjects beginning the study at the contemplation stage of change, intervention subjects reported progressing forward on the stage of change scale for 75.0% (SD, 36.3%) of their health risks compared to 52.1% (SD, 47.1%) in the control group (P = 0.006). CONCLUSION: The scalability of Gabby has the potential to improve women’s nutritional health as an adjunct to clinical care or at the population health level. Further studies are needed to determine if improving nutrition and supplement risks can impact clinical outcomes including optimization of weight. .